2016
DOI: 10.1039/c6cc07771d
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-mediated radical oxydifluoromethylation of olefinic amides for the synthesis of CF2H-containing heterocycles

Abstract: The visible-light-mediated oxydifluoromethylation of olefinic amides with difluoromethyl sulfones has been explored. This method allows for an efficient and practical synthesis of a variety of CFH-containing benzoxazines and oxazolines bearing various functional groups under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(64 citation statements)
references
References 76 publications
1
58
0
Order By: Relevance
“…An examination of the substituent effects in aryl alkenes showed that neither electron-withdrawing nor -donating groups had an obvious impact on the yields.A variety of functional groups were tolerated, such as ether, ester,k etone,c hloride,b romide,i odide,b oronic acid ester, and amide groups.The compatibility of this reaction with the reactive functional groups,i ncluding bromide (4-14, 4-15, 4-24), iodide (4-16), and boronic acid ester (4-12), allowed further CÀCc oupling transformations.T he HCF 2 /CN-containing estrone derivatives were synthesized by this cyanodifluoromethylation conversion, further demonstrating the synthetic utility of this method (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). An examination of the substituent effects in aryl alkenes showed that neither electron-withdrawing nor -donating groups had an obvious impact on the yields.A variety of functional groups were tolerated, such as ether, ester,k etone,c hloride,b romide,i odide,b oronic acid ester, and amide groups.The compatibility of this reaction with the reactive functional groups,i ncluding bromide (4-14, 4-15, 4-24), iodide (4-16), and boronic acid ester (4-12), allowed further CÀCc oupling transformations.T he HCF 2 /CN-containing estrone derivatives were synthesized by this cyanodifluoromethylation conversion, further demonstrating the synthetic utility of this method (4)(5)(6)(7)(8)…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…An examination of the substituent effects in aryl alkenes showed that neither electron-withdrawing nor -donating groups had an obvious impact on the yields.A variety of functional groups were tolerated, such as ether, ester,k etone,c hloride,b romide,i odide,b oronic acid ester, and amide groups.The compatibility of this reaction with the reactive functional groups,i ncluding bromide (4-14, 4-15, 4-24), iodide (4-16), and boronic acid ester (4-12), allowed further CÀCc oupling transformations.T he HCF 2 /CN-containing estrone derivatives were synthesized by this cyanodifluoromethylation conversion, further demonstrating the synthetic utility of this method (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). An examination of the substituent effects in aryl alkenes showed that neither electron-withdrawing nor -donating groups had an obvious impact on the yields.A variety of functional groups were tolerated, such as ether, ester,k etone,c hloride,b romide,i odide,b oronic acid ester, and amide groups.The compatibility of this reaction with the reactive functional groups,i ncluding bromide (4-14, 4-15, 4-24), iodide (4-16), and boronic acid ester (4-12), allowed further CÀCc oupling transformations.T he HCF 2 /CN-containing estrone derivatives were synthesized by this cyanodifluoromethylation conversion, further demonstrating the synthetic utility of this method (4)(5)(6)(7)(8)…”
mentioning
confidence: 91%
“…[2,3] Because difluoromethylation is the most straightforward strategy for incorporation of HCF 2 into organic molecules,m any difluoromethylation reagents have been developed, [4] such as TMSCF 2 H [5] and XCF 2 H( X= F, Cl, or Br). [6] Simultaneous incorporation of as econd functional group into molecules would allow further transformation;t he second functional group could also have excellent potential for the design of pharmaceuticals and agrochemicals.T herefore,m uch effort has been devoted to development of efficient methods for difluoromethylative difunctionalization of alkenes,i ncluding hydrodifluoromethylation, [7] carbodifluoromethylation, [8] oxydifluoromethylation, [9] and halodifluoromethylation. [10] Then itrile group (CN) is av ersatile functionality in synthetic chemistry and life sciences,a nd thus cyanation has received much attention.…”
mentioning
confidence: 99%
“…Recently, an additional example of Ir‐catalyzed formation of benzoxazines and oxazolines through oxydifluoromethylation between olefinic amides and difluoromethyl sulfones was demonstrated by Fu and co‐workers (Scheme and ) . A range of benzoxazines and oxazolines were efficiently furnished by light irradiation from blue LEDs under carefully optimized reaction conditions.…”
Section: Diverse Fluorine Functionalities For π‐Systemsmentioning
confidence: 99%
“…[82] For benzamide derivatives, it appeared that electron-neutral, -donating, and -withdrawing substituents led to very good to excellent yields (401-406). The steric hindrance of the amido substituent did not impact the reaction, and a 2,6-chloro-substituted phenyl ring reacted efficiently to afford 402.…”
Section: Reaction-partner-centered Radical Pathwaymentioning
confidence: 99%